The effect of endurance exercise on intestinal integrity in well‐trained healthy men. Issue 20 (26th October 2016) - JanssenDuijghuijsen, Lonneke M.; Mensink, Marco; Lenaerts, Kaatje; Fiedorowicz, Ewa; ,; van Dartel, Dorien A. M.; Mes, Jurriaan J.; Luiking, Yvette C.; Keijer, Jaap; Wichers, Harry J.; Witkamp, Renger F.; van Norren, Klaske
Abstract: Exercise is one of the external factors associated with impairment of intestinal integrity, possibly leading to increased permeability and altered absorption. Here, we aimed to examine to what extent endurance exercise in the glycogen‐depleted state can affect intestinal permeability toward small molecules and protein‐derived peptides in relation to markers of intestinal function. Eleven well‐trained male volunteers (27 ± 4 years) ingested 40 g of casein protein and a lactulose/rhamnose (L/R) solution after an overnight fast in resting conditions (control) and after completing a dual – glycogen depletion and endurance – exercise protocol (first protocol execution). The entire procedure was repeated 1 week later (second protocol execution). Intestinal permeability was measured as L/R ratio in 5 h urine and 1 h plasma. Five‐hour urine excretion of betacasomorphin‐7 (BCM7), postprandial plasma amino acid levels, plasma fatty acid binding protein 2 (FABP‐2), serum pre‐haptoglobin 2 (preHP2), plasma glucagon‐like peptide 2 (GLP2), serum calprotectin, and dipeptidylpeptidase‐4 (DPP4) activity were studied as markers for excretion, intestinal functioning and recovery, inflammation, and BCM7 breakdown activity, respectively. BCM7 levels in urine were increased following the dual exercise protocol, in the first as well as the second protocol execution, whereas 1 h‐plasma L/R ratio was increased only following the first exercise protocol execution. FABP2, preHP2, and GLP2 were not changed after exercise, whereas calprotectin increased. Plasma citrulline levels following casein ingestion (iAUC) did not increase after exercise, as opposed to resting conditions. Endurance exercise in the glycogen depleted state resulted in a clear increase of BCM7 accumulation in urine, independent of DPP4 activity and intestinal permeability. Therefore, strenuous exercise could have an effect on the amount of food‐derived bioactive peptides crossing the epithelial barrier. The health consequence of increased passage needs more in depth studies. Abstract : This study shows that there is adaptation seen with repeated exercise for intestinal permeability with the classical sugar test. This adaptation is not seen for the increased amount of the betacasomorphin‐7 peptide excreted in urine following strenuous exercise compared to rest.